2011
DOI: 10.1093/cercor/bhq272
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Responses in Visual Area V2 (V2) of Macaque Monkeys with Strabismic Amblyopia

Abstract: Amblyopia, a developmental disorder of spatial vision, is thought to result from a cascade of cortical deficits over several processing stages beginning at the primary visual cortex (V1). However, beyond V1, little is known about how cortical development limits the visual performance of amblyopic primates. We quantitatively analyzed the monocular and binocular responses of V1 and V2 neurons in a group of strabismic monkeys exhibiting varying depths of amblyopia. Unlike in V1, the relative effectiveness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
147
1
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(159 citation statements)
references
References 66 publications
5
147
1
2
Order By: Relevance
“…The treatment is designed to reduce suppression of the amblyopic eye and therefore improve binocular functions, such as stereopsis [11,23]. The fact that monocular function also improves, even though the fellow eye is never occluded during treatment, emphasizes the importance of binocular dysfunction in the visual deficits associated with amblyopia [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment is designed to reduce suppression of the amblyopic eye and therefore improve binocular functions, such as stereopsis [11,23]. The fact that monocular function also improves, even though the fellow eye is never occluded during treatment, emphasizes the importance of binocular dysfunction in the visual deficits associated with amblyopia [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…That study showed that ocular dominance was often balanced between the eyes despite the presence of amblyopia; this was especially true in cases of strabismic amblyopia. Smith and colleagues further showed that there are substantial residual binocular interactions among neurons in V1 and V2 of amblyopic monkeys Bi et al, 2011).…”
Section: Amblyopiamentioning
confidence: 99%
“…To explore the possible contribution of subcortical structures to number processing in humans, we exploit a psychophysical method that allows us to differentiate between cortical vs. subcortical, monocular visual signals before layer IV of primary visual cortex (50)(51)(52). Before this layer, the monocular signals of the visual system are propagated by separate sets of neurons, but beyond layer IV, signals from each eye are no longer segregated, and, because there are relatively few monocular neurons beyond area V1, activation of extrastriate areas is not eye dependent (52).…”
mentioning
confidence: 99%
“…Before this layer, the monocular signals of the visual system are propagated by separate sets of neurons, but beyond layer IV, signals from each eye are no longer segregated, and, because there are relatively few monocular neurons beyond area V1, activation of extrastriate areas is not eye dependent (52). The current work takes advantage of this prestriate separation of signals.…”
mentioning
confidence: 99%